The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.12988/ams.2014.312678
|View full text |Cite
|
Sign up to set email alerts
|

Modified multi-step iterative processes for a finite family of asymptotically pseudocontrative maps

Abstract: Very recently, Mogbademu [6] answered in affirmative the open problem proposed in [9] by extending an iterative algorithm for two asymptotically pseudocontractive mappings to three mappings. He further asked if his results could be extended to the case of finite family of mappings. This sequel gives a positive answer to the open problem and equally extends so many results in this area of research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 10 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Since (i) → (ii) and (ii) → (i), it is shown that the convergence of random implicit Jungck-Kirk-Mann iteration (14) is equivalent to the convergence of random implicit Jungck-Kirk-multistep iteration (11) when applied to a pair of random weakly compatible generalized -contractive-like conditions (19). This ends the proof.…”
Section: Resultsmentioning
confidence: 61%
See 4 more Smart Citations
“…Since (i) → (ii) and (ii) → (i), it is shown that the convergence of random implicit Jungck-Kirk-Mann iteration (14) is equivalent to the convergence of random implicit Jungck-Kirk-multistep iteration (11) when applied to a pair of random weakly compatible generalized -contractive-like conditions (19). This ends the proof.…”
Section: Resultsmentioning
confidence: 61%
“…Since the random implicit Jungck-Kirk-multistep iteration (11) generalizes other random implicit Jungck-Kirk-type iterations (12), (13), and (14), then Theorem 7 leads to the following corollaries.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations